2000
DOI: 10.1136/adc.82.3.244
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of antimony in infants dying from SIDS and infants dying from other causes

Abstract: Objectives-Raised concentrations of antimony have been found in infants dying of sudden infant death syndrome (SIDS). The presumed source of this antimony is toxic gases generated from fire retardants that are present in cot mattresses. The aim of this study was to determine the role of antimony in SIDS. Design-Samples of liver, brain, serum, and urine were collected from all patients dying from SIDS and a group of aged matched control infants who had died of other causes. Setting-Nationwide study in Ireland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In vitro experiments appeared to demonstrate the release of stibine and phosphine, hydrides of antimony oxide fire retardant and phosphorus plasticisers from polyvinyl chloride mattress covers which had been treated with these substances and it was claimed that they had caused deaths from their toxicity. However, urine antimony concentration of antimony in infants dying from SIDS were similar to values found in control infants and healthy infants [24]. This causal role of antimony in SIDS was ultimately refuted due to lack of evidence.…”
Section: Resultsmentioning
confidence: 93%
“…In vitro experiments appeared to demonstrate the release of stibine and phosphine, hydrides of antimony oxide fire retardant and phosphorus plasticisers from polyvinyl chloride mattress covers which had been treated with these substances and it was claimed that they had caused deaths from their toxicity. However, urine antimony concentration of antimony in infants dying from SIDS were similar to values found in control infants and healthy infants [24]. This causal role of antimony in SIDS was ultimately refuted due to lack of evidence.…”
Section: Resultsmentioning
confidence: 93%
“…The hallmark of arsine poisoning is intravascular hemolysis secondary to binding of arsine with oxidized hemoglobin. In a case report of acute arsine poisoning, antimony was detected in the urine of one patient, suggesting the co-formation of stibine through the same mechanism as arsine formation [87]. Although studies of pesticide workers exposed to phosphine demonstrated decreased RBC and pseudocholinesterase activity, suggesting a possible mechanism for stibine toxicity [88], subsequent studies found this to be incorrect [89].…”
Section: Clinical Presentation and Lifethreatening Effectsmentioning
confidence: 97%
“…Several cases of poisoning from a mixture of gases including stibine (others being arsine and hydrogen sulfide) have been reported [87]. The hallmark of arsine poisoning is intravascular hemolysis secondary to binding of arsine with oxidized hemoglobin.…”
Section: Clinical Presentation and Lifethreatening Effectsmentioning
confidence: 98%
“…If the outliers are excluded the results are similar to those seen in non-SIDS deaths. 32,33 Given that the samples had not been collected with the analysis in mind, sample contamination was the obvious likely explanation for the outliers even in 1996.…”
Section: Fire Retardants and Sudden Infant Death Syndromementioning
confidence: 99%